A Hybrid Fixed Point Result for Lipschitz Homomorphisms on Quasi-Banach Algebras (Analysis in Theory and Applications, 2011)
We shall generalize the results of [9] about characterization of isomorphisms on quasi-Banach algebras by providing integral type conditions. Also, we shall give some new results in this way and finally, give a result about hybrid fixed point of two homomorphisms on quasi-Banach algebras.
Keywords: homomorphism; hybrid fixed point; integral-type condition; $p$-norm; quasi-Banach algebra.